The Effect of The Implementation of PBL and Inquiry Models on The Mathematical Literacy Ability - Siti Nujuliya Rohmah; Nizlel Huda; Syaiful (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
The learning techniques applied during the independent curriculum era require learning innovations that will be applied in learning, one of which is by implementing the PBL learning model and also the Inquiry model, where the application usually uses the direct instruction model. This study explains how the influence of students' mathematical literacy skills with the material taught, namely algebraic forms, with the learning model applied in each predetermined experimental class. True Experimental Design is a learning method used by researchers, Pretest-Posttest Control Group Design is the data obtained used by researchers. The results of the study found that the application of the inquiry learning model tends to provide a greater tendency towards students ' mathematical literacy skills compared to PBL and direct learning. In accordance with the results of the one-way ANOVA test and Tukey's follow-up test. The significant results obtained from the similarity test showed an increase in students' mathematical literacy skills, namely 0.727> 0.05. The hypothesis was found accepted, with the results of the difference in the average influence of students' mathematical literacy test scores on the application of PBL, inquiry, and direct instruction learning models.